Translation and psychometric evaluation of the Chinese version of the Nursing Time Management Scale - Fu, Zhaoquan; Wang, Yaping; Zhang, Limei; Tan, Mingyang (Frontiers in Medicine, 2024)
Background Reasonable and effective time allocation can promote the improvement of medical care service quality. This study aimed to translate, cross-culturally adapt and validate the Chinese Nursing Time Management Scale (NTMS). Methods Using a cross-sectional survey, 345 clinical nurses were selected from June to September 2023 for a general information questionnaire and Nursing Time Management Scale (NTMS) study. Item analysis, exploratory factor analysis and validation factor analysis were used to verify the reliability and validity of the Chinese version of Nursing Time Management Scale. Results The Chinese version of the Nurses’ Time Management Competency Scale includes 17 entries in 3 dimensions: planning activities and setting goals, coordinating activities and procedures, and organizing nursing activities. The Cronbach’s alpha coefficient for the total scale was 0.966. Exploratory factor analysis showed that the cumulative variance contribution of the three male factors was 97.44%. Conclusion The NTMS has acceptable validity and reliability and can be used to evaluate the nursing time management skills of Chinese clinical nurses.